Efektifitas penerapan interprofessional education-collaborative practice (IPE–CP) tentang gizi seimbang terhadap pengetahuan dan sikap ibu hamil - Sudarmi Sudarmi; Bertalina Bertalina; Aprina Aprina (Jurusan Gizi Politeknik Kesehatan Kemenkes Aceh, 2020)
The behavior of a pregnant mother to consume healthy food, including the quality and quantity of food that is diverse and balanced according to the needs during pregnancy, is very desirable. Effective education to deliver a balanced nutrition message requires an Interprofessional Educative Collaboration Practice (IPE-CP) approach. The involvement of various professions is thought to be effective in increasing mothers' knowledge and attitudes about balanced nutrition. The purpose of this study was to determine the effect of the application of IPE-CP on balanced nutrition on the knowledge and attitude of a pregnant mother. The research is a quasi-experimental one-group pretest-posttest design. Samples were taken as many as 60 pregnant women using the Federer formula. Interventions in the form of education and assistance on balanced nutrition provided by the application of IPE-CP. Data is taken by pre-test and post-test questions about balanced nutrition. Data analyzed using the Dependent T-test and the Cohen Effect test. The results showed that there was a significant influence on the application of IPE-CP to maternal knowledge (p=0,003), maternal attitudes (p=0,000) about balanced nutrition. The most influential effect size is the mother's attitude (0,92), so it has a big effect. In conclusion, IPE-CP is very effective in increasing the knowledge and attitude of pregnant women about balanced nutrition. Suggestions for health workers to be able to implement IPE-CP in solving nutrition problems. Perilaku ibu hamil untuk mengkonsumsi makanan sehat, mencakup kualitas maupun kuantitas makanan yang beragam dan berimbang sesuai dengan kebutuhan di masa kehamilannya sangatlah diharapkan. Edukasi yang efektif untuk menyampaikan pesan gizi seimbang diperlukan strategi pendekatan Interprofessional Educatif Calaboration Practice (IPE-CP). Keterlibatan berbagai profesi diduga efektif untuk meningkatkan pengetahuan dan sikap ibu tentang gizi seimbang. Tujuan penelitian untuk mengetahui pengaruh penerapan IPE-CP tentang gizi seimbang terhadap pengetahuan dan sikap ibu hamil. Jenis penelitian kuasi eksperimen rancangan one group pretest–posttest design. Sampel 60 ibu hamil diperoleh berdasarkan perhitungan rumus Federer. Intervensi berupa edukasi dan pendampingan tentang gizi seimbang yang diberikan dengan penerapan IPE-CP. Data diambil dengan pre-test dan post-tes soal tentang gizi seimbang. Data dianalisis menggunakan uji Dependent T-test serta uji cohen effect. Hasil menunjukkan terdapat pengaruh signifikan penerapan IPE-CP terhadap pengetahuan ibu (p= 0,003), sikap ibu (p= 0,000) tentang gizi seimbang. Effect Size yang paling berpengaruh yaitu sikap ibu (0,92) sehingga berpengaruh besar. Kesimpulan, IPE-CP sangat efektif untuk meningkatkan pengetahuan dan sikap ibu hamil tentang gizi seimbang. Saran, kepada petugas kesehatan untuk dapat menerapkan IPE-CP dalam memecahkan masalah gizi ibu hamil.